Diagnosing the reality and importance of the tourism sector and trying to address its shortcomings in Algeria - Rabeh, Fadhil; Hafsi, Yacine (Dirassat Journal Economic Issue, 2017)
The tourism sector is considered to be one of the most strategic sectors, in recent times given its importance and its influence on individuals, societies and the economy of countries. For Algeria, and despite the capacities and opportunities it has in this area, it has not been able to invest in tourism, and so far, it is far from the requirements of the world market in this sector. The studies developed in this context have made it possible to give definitions and general conceptions on tourism, the role and economic importance in the tourism sector, the influences of the tourism sector on the global and territorial level, diagnosis of the situation. of this sector in Algeria through the exposure of tourism projects, the volume of tourist flows and the state’s financial income in this sector and its influence on the economy and society, in addition to determining the appropriate strategy for the evolution of this sector, and ultimately draw conclusions and suggest solutions to improve the tourism sector in Algeria.